The trend over time of the gender wage gap in Italy - Chiara Mussida; Matteo Picchio (Institute for the Study of Labor (IZA), 2011)
We analyse gender wage inequalities in Italy in the mid-1990s and in the mid-2000s. In this period important labour market developments occurred: institutional changes have loosened the use of flexible and atypical contracts; the female employment rates and educational levels have substantially increased. We identify the time trends of different components of the gender wage gap by estimating wage distributions in the presence of covariates and sample selection and by counterfactual microsimulations. We find that women swam against the tide: whilst the trend in female qualifications slightly reduced the gender wage gap, the gender relative trends in the wage structure significantly increased it.
urn:nbn:de:101:1-201109286254
Keywords: C21; C41; J16; J31; J71; 330; gender wage gap; counterfactual distributions; decompositions; hazard function; labour market reforms; Lohndifferenzierung; Geschlecht; Arbeitsmarktpolitik; Verteilungswirkung; Italien